Six-Month Effectiveness of Remote Activity Monitoring for Persons Living With Dementia and Their Family Caregivers: An Experimental Mixed Methods Study. (5th July 2018) - Gaugler, Joseph E; Zmora, Rachel; Mitchell, Lauren L; Finlay, Jessica M; Peterson, Colleen M; McCarron, Hayley; Jutkowitz, Eric
Abstract: Background and Objectives: This study aimed to evaluate if and how remote activity monitoring (RAM) improves caregiver outcomes for family members providing care for persons living with Alzheimer's disease or a related dementia (ADRD). Research Design and Methods: We conducted an embedded experimental mixed methods study of 132 persons living with ADRD and their family caregivers ( n = 64 randomly assigned to RAM treatment condition). In addition to baseline and 6-month quantitative survey data on context of care, primary objective stressors, resources, self-efficacy/competence, and distress collected from caregivers, 6-month RAM review checklists contained open-ended, qualitative information on perceived acceptability of the technology. Results: The RAM system did not exert statistically significant effects on caregiving outcomes over a 6-month period. However, qualitative analyses identified several potential moderators of RAM technology effectiveness that were subsequently tested in post-hoc repeated measures analyses of variance. Caregivers who utilized RAM technology and cared for relatives with: (a) less severe cognitive impairment; and (b) difficulty navigating around the home were more likely to indicate statistically significant increases in competence and self-efficacy, respectively. Discussion and Implications: We found that the early months spent calibrating and modifying RAM are potentially challenging for families, which may prevent this technology from improving caregiving outcomes during initial months of use. Remote activity monitoring may work optimally for caregivers of persons living with ADRD in specific situations (e.g., earlier stages of dementia; wandering risk), which suggests the need for appropriate needs assessments that can better target such innovations.